Composite shell surface coating and composite shell

By using composite shell coating in the directional solidification process, the sand sticking problem caused by the chemical reaction between the high-temperature alloy and the shell surface is solved, the finish and quality of the casting surface are improved, and the pass rate of the casting is improved.

CN115041629BActive Publication Date: 2025-03-25GAONA AERO MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210750781.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2025-03-25
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

In the directional solidification process, the chemical reaction between the high-temperature alloy and the molded shell surface layer causes a sand sticking layer to appear on the surface of the casting, which increases the workload of subsequent grinding and may cause dimensional scrapping.

Method used

A composite shell coating is used, which includes sintered zircon powder and silicon sol, which has excellent stability and fluidity, and does not react chemically with the alloy at high temperatures. This coating is used to prepare composite shells, which reduces the chemical reaction between the inner wall of the shell and the high-temperature alloy through specific hierarchical structures and material combinations.

Benefits of technology

It effectively reduces the degree of sand sticking on the surface of high-temperature alloy castings, improves the surface finish and quality of the castings, and significantly improves the qualification rate of the castings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of casting technology, and in particular to a composite shell surface coating and a composite shell. The composite shell surface coating of the present invention comprises powder and silica sol; the powder comprises sintered zircon powder; the sintering temperature is 1590-1610°C, and the sintering time is 3-10 hours. The composite shell surface coating has excellent stability and fluidity, and does not chemically react with the alloy at high temperature; it can effectively reduce the chemical reaction between the inner wall of the shell and the high-temperature alloy, and reduce the degree of sand adhesion on the surface of the high-temperature alloy casting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of casting, in particular to a composite shell surface coating and a composite shell. Background Art

[0002] Directional solidification, also known as directional crystallization, refers to a process method that allows metals or alloys to grow crystals in a molten state in a directional manner. Directional solidification technology is a process that establishes a temperature gradient in a specific direction in the casting mold, so that the molten alloy is solidified and cast in the opposite direction of the heat flow according to the required crystal orientation. It can greatly improve the comprehensive performance of high-temperature alloys. Directional solidification parts are usually made into ceramic mold shells first, and then the molten metal is poured and pulled to cool to form a directional solidification structure casting. Among them, the shell material is usually made of corundum powder, corundum sand, zircon powder and other materials; the pouring temperature in the directional pouring process is high, the solidification time of the casting is long, and the metal is easy to react chemically with the shell surface at high temperature, forming an uneven "sand sticking layer" on the surface of the casting, which increases the workload of subsequent grinding and seriously causes the size to be scrapped.

[0003] Existing technologies for solving the problem of surface sand adhesion include using a pickling method to remove mechanical iron in bauxite and make mold shell surface materials, but this process cannot solve the problem of surface sand adhesion on cobalt-based alloy castings such as DZ40M.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a composite shell surface coating, which has excellent stability and fluidity and does not chemically react with the alloy at high temperature.

[0006] The second object of the present invention is to provide a composite mold shell, which can effectively reduce the chemical reaction between the inner wall of the mold shell and the high-temperature alloy, reduce the degree of sand adhesion on the surface of the high-temperature alloy casting, and greatly improve the qualified rate of the casting.

[0007] The third object of the present invention is to provide an application of a composite shell in a high-temperature alloy directional solidification process, which reduces the degree of sand adhesion on the surface of high-temperature alloy castings, such as cobalt-based alloy castings, especially DZ40M alloy castings, and improves the smoothness of the casting surface.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention provides a composite shell surface coating, comprising powder and silica sol;

[0010] The powder material includes sintered zircon powder;

[0011] The sintering temperature is 1590-1610° C., and the sintering time is 3-10 hours.

[0012] Furthermore, the powder material includes, by weight, 30 to 40 parts of sintered zircon powder with a particle size of 1 to 80 μm, 40 to 50 parts of sintered zircon powder with a particle size of 1 to 60 μm, and 10 to 30 parts of sintered zircon powder with a particle size of 1 to 40 μm.

[0013] Furthermore, the mass ratio of the powder to the silica sol is 4-5:1.

[0014] Furthermore, the viscosity of the composite shell surface coating is 45 to 60 seconds.

[0015] The present invention also provides a composite shell, comprising a surface layer, a first sand-spreading layer, a transition layer, a second sand-spreading layer, a reinforcement layer and a sealing layer connected in sequence;

[0016] The surface layer comprises the composite shell surface coating according to any one of claims 1 to 4.

[0017] Furthermore, the first sand spreading layer includes zircon sand.

[0018] Further, the transition layer includes corundum powder;

[0019] Furthermore, the second sanding layer includes corundum sand.

[0020] Furthermore, the reinforcement layer includes alternatingly arranged corundum powder coating layers and corundum sand layers.

[0021] Preferably, the number of the corundum powder coating layers is 4 to 6.

[0022] Furthermore, the sealing layer includes corundum powder.

[0023] The present invention also provides application of the composite shell in a high-temperature alloy directional solidification process.

[0024] Preferably, the high temperature alloy comprises a cobalt-based alloy.

[0025] Preferably, the cobalt-based alloy comprises DZ40M alloy.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The composite mold shell surface coating provided by the present invention has excellent stability and fluidity, does not chemically react with the alloy at high temperatures, and the composite mold shell prepared by using the composite mold shell surface coating has good surface uniformity, which can effectively reduce the chemical reaction between the inner wall of the mold shell and the high-temperature alloy, reduce the degree of sand adhesion on the surface of the high-temperature alloy casting, and improve the surface finish and surface quality of the casting.

[0028] (2) Compared with ordinary mold shells, the composite mold shell provided by the present invention has high mold shell strength and good high-temperature stability. The surface of the casting obtained by the directional solidification process using the composite mold shell is bright and has no reaction layer, which greatly improves the qualified rate of the casting; in particular, it improves the surface finish of cobalt-based alloys, such as DZ40M alloy. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] The following is a detailed description of a composite shell surface coating and a composite shell according to an embodiment of the present invention.

[0031] In some embodiments of the present invention, a composite shell surface coating is provided, including powder and silica sol;

[0032] The powder material includes sintered zircon powder;

[0033] The sintering temperature is 1590-1610°C, and the sintering time is 3-10 hours.

[0034] The composite mold shell surface coating provided by the present invention has excellent stability, does not chemically react with the alloy at high temperature, can effectively reduce the chemical reaction between the inner wall of the mold shell and the high-temperature alloy, reduces the degree of sand adhesion on the surface of the high-temperature alloy casting, and improves the surface finish of the casting.

[0035] In some embodiments of the present invention, typically but not limitatively, for example, the sintering temperature is 1590°C, 1595°C, 1600°C, 1605°C and 1610°C; the sintering time is 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.

[0036] In some embodiments of the present invention, sintering comprises heating zircon powder to 1590-1610°C and keeping it for 3-10 hours, then furnace cooling to 800°C and air cooling; preferably, the zircon powder is first-grade zircon powder, which is usually calcined at 650°C.

[0037] The present invention sintered zircon powder at 1590-1610°C, which can fully burn out impurities in the zircon powder. More importantly, the zircon powder is decomposed into stable zirconium oxide at about 1300°C, and the decomposed unstable SiO2 is stabilized to prevent decomposition during the casting process (1450-1500°C) and reaction with the alloy.

[0038] In some embodiments of the present invention, the powder material includes, by weight: 30 to 40 parts of sintered zircon powder with a particle size of 1 to 80 μm, 40 to 50 parts of sintered zircon powder with a particle size of 1 to 60 μm, and 10 to 30 parts of sintered zircon powder with a particle size of 1 to 40 μm.

[0039] In some embodiments of the present invention, the sintering process of the sintered zircon powder with a particle size of 1 to 80 μm, the sintered zircon powder with a particle size of 1 to 60 μm, and the sintered zircon powder with a particle size of 1 to 40 μm are the same.

[0040] Zircon powder is an industrial material used for casting coatings and ceramic cores in the investment casting (precision casting) industry; its chemical composition includes: ZrO2>65wt%, SiO2<33wt%, TiO2<0.4wt%, Fe2O3<0.5wt%, P2O5<0.5wt% and Al2O3<0.3wt%; particle size: 95% passes 320 mesh, and the rest passes 260 mesh.

[0041] In some embodiments of the present invention, in the powder material, the amount of sintered zircon powder with a particle size of 1 to 80 μm can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, etc.; the amount of sintered zircon powder with a particle size of 1 to 60 μm can be 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts, etc.; the amount of sintered zircon powder with a particle size of 1 to 40 μm can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, etc.

[0042] In some embodiments of the present invention, the method for preparing the powder comprises the following steps:

[0043] The mixture of zircon balls, sintered zircon powder and water is ball-milled, sieved and dried to obtain powder; preferably, the sieving includes filtering the powder with a 200-mesh screen; preferably, the drying temperature is 100-200° C. and the drying time is 1-3 hours.

[0044] In some embodiments of the present invention, in the method for preparing the powder, the mass ratio of the zircon balls, the sintered zircon powder and water is 1.5-1.7:1:0.5-0.7.

[0045] In some embodiments of the present invention, in the powder preparation method, a mixture of zircon balls, sintered zircon powder and water is ball-milled at a speed of 1000 rpm for 20 to 24 hours, and then sieved and dried to obtain a powder with a particle size of 1 to 80 μm, which is named the first powder.

[0046] In some embodiments of the present invention, in the powder preparation method, a mixture of zircon balls, sintered zircon powder and water is ball-milled at a speed of 1000 rpm for 40 to 48 hours, and then sieved and dried to obtain a powder with a particle size of 1 to 60 μm, which is named the second powder.

[0047] In some embodiments of the present invention, in the powder preparation method, a mixture of zircon balls, sintered zircon powder and water is ball-milled at a speed of 1000 rpm for 55 to 60 hours, and then sieved and dried to obtain a powder with a particle size of 1 to 40 μm, which is named the third powder.

[0048] In some embodiments of the present invention, the mass ratio of powder to silica sol is 4-5:1; typically but not limiting, for example, the mass ratio of powder to silica sol is 4:1, 4.5:1 or 5:1, etc.

[0049] In the present invention, the use of the powder and silica sol in the above mass ratio can make the composite shell surface coating have excellent fluidity and improve the uniformity of the surface layer.

[0050] In some embodiments of the present invention, the viscosity of the composite shell surface coating is 45-60s. The viscosity is tested by measuring at 22°C ± 2°C using a 4# Zahn cup.

[0051] In some embodiments of the present invention, a method for preparing a composite shell surface coating comprises the following steps:

[0052] The powder is slowly added into the silica sol to obtain a composite shell surface coating with a viscosity of 45 to 60 seconds.

[0053] During the use of the composite shell surface coating, due to the change in viscosity caused by the volatilization of water, the viscosity of the composite shell surface coating can be adjusted to 45-60s by adding water.

[0054] In some embodiments of the present invention, a composite shell is provided, comprising a surface layer, a first sanding layer, a transition layer, a second sanding layer, a reinforcement layer and a sealing layer connected in sequence;

[0055] The surface layer includes the above-mentioned composite shell surface coating.

[0056] In some embodiments of the present invention, the first sand spreading layer includes zircon sand; preferably, the zircon sand includes 80-100# zircon sand.

[0057] In some embodiments of the present invention, the transition layer includes corundum powder; preferably, the corundum powder includes 270-320# corundum powder.

[0058] In some embodiments of the present invention, the second sanding layer includes corundum sand; preferably, the corundum sand includes 60-80# corundum sand.

[0059] In some embodiments of the present invention, the reinforcement layer includes alternating corundum powder coating layers and corundum sand layers; preferably, the corundum powder includes 270-320# corundum powder; and the corundum sand includes 24-36# corundum sand.

[0060] In some embodiments of the present invention, the second sanding layer is connected to the corundum powder coating layer.

[0061] In some embodiments of the present invention, in the reinforcement layer, the number of corundum powder coating layers is 4 to 6 layers; the number of corundum sand layers is 4 to 6 layers; the number of corundum coating layers is the same as the number of corundum sand layers.

[0062] In some embodiments of the present invention, the sealing layer includes corundum powder; preferably, the corundum powder includes 270-320# corundum powder.

[0063] The composite shell provided by the invention adopts a specific surface coating, and after a directional solidification process of the composite shell obtained through processes such as slurry dipping, sand hanging, dewaxing, and roasting, the surface of the casting is bright and has no sand sticking reaction.

[0064] In some embodiments of the present invention, a method for preparing a composite shell comprises the following steps:

[0065] (A) coating the composite shell surface coating on the wax film surface, and obtaining the surface layer after coating evenly; sanding and drying the surface of the surface layer to obtain the first sanding layer;

[0066] (B) coating the surface of the first sand-sprinkling layer with the slurry of the transition layer, and evenly coating the surface to obtain the transition layer; and sanding and drying the surface of the transition layer to obtain the second sand-sprinkling layer;

[0067] (C) coating the surface of the second sand-sprinkled layer, coating evenly, sand-sprinkling and drying to obtain a reinforcement layer;

[0068] (D) coating the surface of the reinforcement layer with a sealant slurry and drying the slurry to obtain a shell;

[0069] (E) The shell is dewaxed and then calcined to obtain a composite shell.

[0070] In some embodiments of the present invention, in step (A), the drying temperature is 20-30° C., and the drying time is 20-30 h; preferably, the drying humidity is 60%-70%.

[0071] In some embodiments of the present invention, in step (B), the slurry of the transition layer includes corundum powder and silica sol; preferably, the viscosity of the slurry of the transition layer is 8 to 12 seconds.

[0072] In some embodiments of the present invention, in step (B), the drying temperature is 20 to 30° C., and the drying time is 6 to 8 hours.

[0073] In some embodiments of the present invention, in step (C), paint is applied on the surface of the second sanding layer, and after the paint is applied evenly, sanding and drying are performed, and then the paint application is repeated, and after the paint is applied evenly, sanding and drying are performed 3 to 5 times.

[0074] In some embodiments of the present invention, in step (C), the coating comprises corundum powder and silica sol; preferably, the viscosity of the coating is 12 to 18 seconds.

[0075] In some embodiments of the present invention, in step (C), drying comprises air drying; preferably, the drying time is 4 to 6 hours.

[0076] In some embodiments of the present invention, in step (D), the slurry of the sealing layer includes corundum powder and silica sol; preferably, the viscosity of the slurry of the sealing layer is 12 to 18 seconds.

[0077] In some embodiments of the present invention, in step (D), the drying time is 20 to 30 hours.

[0078] In some embodiments of the present invention, in step (E), the pressure of the dewaxing treatment is 0.6-0.8 MPa, and the dewaxing time is 10-15 min.

[0079] In some embodiments of the present invention, in step (E), the dewaxing treatment includes dewaxing in an electric steam dewaxing kettle.

[0080] In some embodiments of the present invention, in step (E), the calcination temperature is 1000-1100° C., and the calcination time is 2-4 hours; preferably, the heating rate during the calcination process is 20-30° C. / min.

[0081] In some embodiments of the present invention, application of a composite shell in a high-temperature alloy directional solidification process is also provided.

[0082] In some embodiments of the present invention, the high temperature alloy comprises a cobalt-based alloy.

[0083] In some embodiments of the present invention, the cobalt-based alloy comprises DZ40M alloy.

[0084] DZ40M alloy (DZ640M) includes, by mass fraction, C 0.45%-0.55%, Cr 24.5%-26.5%, Ni 9.5%-11.5%, W 7%-8%, Mo 0.1%-0.5%, Al 0.7%-1.2%, Ti 0.05%-0.3%, Ta 0.1%-0.5%, B 0.008%-0.018%, Zr 0.1%-0.3%, Fe≤2%, Si≤1%, Mn≤1%, P≤0.04%, S≤0.04%, Pb≤0.0005%, Sb≤0.001%, As≤0.04%, Sn≤0.001%, Bi≤0.00005%, and the balance is Co.

[0085] When using conventional ceramic shells, after the DZ40M alloy undergoes a directional solidification process at 1400-1600°C, a layer of reaction products between the alloy and the shell often appears on the surface of the casting, affecting the subsequent product quality and, in severe cases, causing the casting to be scrapped.

[0086] After the composite shell of the present invention is subjected to a 1500° C. directional solidification process, the DZ40M alloy casting obtained has a bright surface and no reaction layer, which can greatly improve the qualified rate of the castings.

[0087] Example 1

[0088] The preparation method of the composite shell surface coating provided in this embodiment comprises the following steps:

[0089] The first-grade zircon powder is heated to 1600°C and kept at this temperature for 5 hours, then cooled in the furnace to 800°C and then air-cooled to obtain sintered zircon powder;

[0090] A mixture of zircon balls, sintered zircon powder and water in a mass ratio of 1.618:1:0.6118 was ball-milled at a speed of 1000 rpm for 24 hours, 48 ​​hours and 55 hours respectively, filtered through a 200-mesh sieve, and dried at 150° C. for 2 hours to obtain a first powder with a particle size of 1 to 80 μm, a second powder with a particle size of 1 to 60 μm and a third powder with a particle size of 1 to 40 μm;

[0091] To 50 kg of silica sol, 60 kg of the third powder, 80 kg of the second powder and 60 kg of the first powder were added in sequence, and stirred for 24 hours to obtain a composite shell surface coating with a viscosity of 50±2s.

[0092] Example 2

[0093] The preparation method of the composite shell surface coating provided in this embodiment comprises the following steps:

[0094] The first-grade zircon powder is heated to 1600°C and kept at this temperature for 8 hours, then cooled in the furnace to 800°C and then air-cooled to obtain sintered zircon powder;

[0095] A mixture of zircon balls, sintered zircon powder and water in a mass ratio of 1.618:1:0.6118 was ball-milled at a speed of 1000 rpm for 20 h, 42 h and 60 h respectively, filtered through a 200-mesh sieve, and dried at 150° C. for 2 h to obtain a first powder with a particle size of 1 to 80 μm, a second powder with a particle size of 1 to 60 μm and a third powder with a particle size of 1 to 40 μm;

[0096] 40 kg of the third powder, 100 kg of the second powder and 60 kg of the first powder were added to 40 kg of silica sol in sequence, and stirred for 24 hours to obtain a composite shell surface coating with a viscosity of 55±5s.

[0097] Example 3

[0098] The method for preparing the composite shell provided in this embodiment comprises the following steps:

[0099] (A) applying a composite shell surface coating on the wax film surface, and obtaining a surface layer after the coating is evenly applied; after sanding the surface of the surface layer with 80-100# zircon sand, the surface is naturally dried for 24 hours in an environment of 22°C±2°C and a humidity of 65%±5%, to obtain a first sanding layer; wherein the composite shell surface coating is the composite shell surface coating obtained in implementation 1;

[0100] (B) coating the transition layer slurry on the surface of the first sanding layer, and obtaining the transition layer after coating evenly; coating the surface of the transition layer with 60# corundum sand, and drying it naturally for 6 to 8 hours at 22°C ± 2°C and 65% ± 5% humidity to obtain the second sanding layer; wherein the preparation method of the transition layer slurry comprises: slowly adding 320# corundum powder to silica sol until the viscosity of the transition layer slurry is 8 to 12s;

[0101] (C) coating the surface of the second sanding layer, coating evenly, sanding with 24# corundum sand, and air-drying for 4-6 hours; repeating the above steps of coating evenly, sanding with 24# corundum sand, and air-drying for 4-6 hours for 5 times to obtain a reinforcement layer; wherein the coating preparation method comprises: slowly adding 320# corundum powder to silica sol until the viscosity of the coating is 12-18s;

[0102] (D) coating the sealing layer slurry on the surface of the reinforcement layer, and drying for 24 hours to obtain a shell; wherein the preparation method of the sealing layer slurry comprises: slowly adding 320# corundum powder to silica sol until the viscosity of the sealing layer slurry is 12 to 18 seconds;

[0103] (E) After the shell is dewaxed in an electric steam dewaxing kettle, it is placed in a sliding bottom resistance furnace, heated to 1000°C ± 20°C at a rate of 20 to 30°C / min, and kept warm for 3 hours to obtain a composite shell; wherein the dewaxing parameters are a pressure of 0.6 to 0.8 MPa and a dewaxing time of 10 to 15 minutes.

[0104] Example 4

[0105] The preparation method of the composite shell provided in this embodiment refers to Example 3, except that in step (A), the composite shell surface coating is the composite shell surface coating prepared in Example 2; in step (C), the above-mentioned coating is repeated, and after the coating is evenly coated, 24# corundum sand is sprinkled, and the reinforcing layer is obtained by air-drying for 4 to 6 hours.

[0106] Comparative Example 1

[0107] The preparation method of the composite shell provided in this comparative example comprises the following steps:

[0108] (A) applying a composite shell surface coating on the wax film surface, and obtaining a surface layer after the coating is evenly applied; after the surface layer is sprinkled with 80# zircon sand, the surface is naturally dried for 24 hours at 22°C±2°C and 65%±5% humidity to obtain a first sanding layer; wherein the preparation method of the composite shell surface coating comprises: slowly adding 150kg of 325# zircon powder to 50kg of silica sol, and stirring for 24 hours to obtain a composite shell surface coating with a viscosity of 45±5s;

[0109] (B) Wetting the surface of the first sanding layer in silica sol, taking it out and coating the slurry of the transition layer, and obtaining the transition layer after coating evenly; sanding the surface of the transition layer with 60# corundum sand, and drying it naturally for 6 to 8 hours at 22°C ± 2°C and 65% ± 5% humidity to obtain the second sanding layer; wherein the preparation method of the slurry of the transition layer comprises: slowly adding 320# corundum powder to the silica sol until the viscosity of the slurry of the transition layer is 12 to 18s;

[0110] (C) coating the surface of the second sanding layer, coating evenly, sanding with 24# corundum sand, and air-drying for 4-6 hours; repeating the above steps of coating evenly, sanding with 24# corundum sand, and air-drying for 4-6 hours for 5 times to obtain a reinforcement layer; wherein the coating preparation method comprises: slowly adding 320# corundum powder to silica sol until the viscosity of the coating is 12-18s;

[0111] (D) coating the sealing layer slurry on the surface of the reinforcement layer, and drying for 24 hours to obtain a shell; wherein the preparation method of the sealing layer slurry comprises: slowly adding 320# corundum powder to silica sol until the viscosity of the sealing layer slurry is 12 to 18 seconds;

[0112] (E) After the shell is dewaxed in an electric steam dewaxing kettle, it is placed in a sliding bottom resistance furnace, heated to 980°C ± 20°C at a rate of 20 to 30°C / min, and kept warm for 3 hours to obtain a composite shell; wherein the dewaxing parameters are a pressure of 0.6 to 0.8 MPa and a dewaxing time of 10 to 15 minutes.

[0113] Comparative Example 2

[0114] The preparation method of the composite shell provided in this embodiment refers to Comparative Example 1, except that the preparation method of the composite shell surface layer coating in step (A) comprises: slowly adding 200 kg of 320# corundum powder to 50 kg of silica sol, stirring for 24 hours to obtain a composite shell surface layer coating with a viscosity of 45±5s; in step (C), repeating the above-mentioned coating, applying the coating evenly, sprinkling 24# corundum sand, and air-drying for 4 to 6 hours for 4 times to obtain a reinforcement layer.

[0115] Test Example 1

[0116] The composite shells prepared in Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were respectively used to pour DZ40M alloy at 1480° C.±10° C. in a directional solidification furnace, and the crystallizer was pulled downward at 6 mm / min.

[0117] The castings obtained by casting the DZ40M alloy with the composite shell of Example 3 and Example 4 have smooth surfaces without sand adhesion reaction; while the castings obtained by casting the DZ40M alloy with the composite shell of Comparative Example 1 and Comparative Example 2 have obvious sand adhesion reaction on the surface.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite shell for directional solidification of DZ40M alloy, characterized in that: The steps include: (A) coating the composite shell surface coating on the wax film surface, and obtaining the surface layer after coating evenly; sanding and drying the surface of the surface layer to obtain the first sanding layer; (B) coating the transition layer slurry on the surface of the first sanding layer to obtain a transition layer after coating evenly; The surface of the transition layer is sanded and dried to obtain a second sanded layer; (C) coating the surface of the second sanding layer, and after coating evenly, sanding and drying are performed, and then the coating is repeated, and after coating evenly, sanding and drying are performed 3 to 5 times to obtain a reinforcement layer; (D) coating the surface of the reinforcement layer with a sealant slurry and drying the slurry to obtain a shell; (E) the shell is dewaxed and then calcined to obtain a composite shell; In step (A), the composite shell surface coating is powder and silica sol, and the mass ratio of the powder to the silica sol is 4 to 5:1; The powder material includes sintered zircon powder, and the zircon powder is first-grade zircon powder; The sintering temperature is 1590-1610°C, and the sintering time is 3-10h; The powder material comprises, by weight, 30 to 40 parts of sintered zircon powder with a particle size of 1 to 80 μm, 40 to 50 parts of sintered zircon powder with a particle size of 1 to 60 μm, and 10 to 30 parts of sintered zircon powder with a particle size of 1 to 40 μm; The viscosity of the composite shell surface coating is 45 to 60 seconds; The first sand spreading layer includes 80-100# zircon sand; In step (B), the slurry of the transition layer includes 270-320# corundum powder and silica sol; the viscosity of the slurry of the transition layer is 8-12s; The second sanding layer includes 60-80# corundum sand; In step (C), the coating comprises 270-320# corundum powder and silica sol; the viscosity of the coating is 12-18s; The sand spreading includes spreading 24-36# corundum sand; In step (D), the slurry of the sealing layer includes 270-320# corundum powder and silica sol; the viscosity of the slurry of the sealing layer is 12-18s; In step (E), the dewaxing treatment includes dewaxing in an electric steam dewaxing kettle; the dewaxing pressure is 0.6-0.8 MPa, and the dewaxing time is 10-15 min; The calcination temperature is 1000-1100° C., the calcination time is 2-4 hours, and the heating rate during the calcination process is 20-30° C. / min.

Citation Information

Patent Citations

  • Sand penetration-preventing alcohol-based foundry coating for resin-bonded sand molds and preparation method thereof

    CN103551498A

  • High-performance ceramic mold shell for directional solidification, and production technology thereof

    CN104772429A

  • Preparation method of hollow blade ceramic core mineralizer for aero-engine

    CN112592177A